AB1285 Ultrasound of MCP- and PIP-joints in rheumatoid arthritis: Increased value of the dorsal approach compared to the volar approach. (23rd January 2014) - Witt, M.; Mueller, F.; Nigg, A.; Reindl, C.; Schulze-Koops, H.; Gruenke, M.
Abstract : Background: Ultrasound is more sensitive for the detection of synovitis than clinical examination in patients with rheumatoid arthritis (RA). However, different examination techniques may result in different sensitivities and specificities of both greyscale (GSUS) and power Doppler ultrasound (PDUS). As sonographic joint assessments increasingly influence our understanding and documantation of disease remission and thus guide our therapeutic decisions, a valid ultrasound assessment is critical. Objectives: To investigate on a large scale the relevance of a volar versus a dorsal sonographic approach using GSUS and PDUS in MCP and PIP joints of patients with RA. Methods: The MCP- and PIP-joints of 100 RA patients were assessed clinically for tenderness and swelling according to the EULAR examination technique. All joints were then independently evaluated by GSUS and PDUS modes with an 18 MHz high resolution device for capsule swelling and synovial hyperperfusion. The ultrasound examination was performed from the volar and dorsal aspect for each MCP- and PIP joint. Both approaches were compared. Statistical analysis was perfomed using Prism 5 for Mac OS X software. Significances were calculated with Fisher's exact test and two-way ANOVA analysis. P values of less than 0.05 were considered statistically significant. Results: Joint swelling as defined by detection of capsule distension in GSUS was found significantly more frequent using the volar approach both in MCP- and PIP joints (40% volar versus 29.3% dorsal, p<0.05). In contrast, significantly more PDUS positive joints were detected in both joint regions by the dorsal approach (3.9% volar versus 14.8% dorsal, p<0.05). Looking at all PDUS positive joints, grade 2 and grade 3 findings account for 41.8% and 19.2% on the dorsal side, and for 11.8% and 6.6% on the volar side, respectively. Subgroup analyses further showed, that the dorsal PDUS approach better reflected clinical disease activity as measured by the DAS28 (p<0.05). Comparing early and established rheumatoid arthritis, the dorsal approach detected significantly more PDUS activity in the early population, while the volar examination showed no differences between these groups. Conclusions: MCP and PIP joints are the most relevant joint regions in patients with RA. While the volar view on these joints seems to be more sensitive for the detection of joint swelling, the more important classification of synovitic activity by PDUS was better determined from the dorsal aspect. An explanation might be, that the thicker soft tissue of the volar side allows GSUS to pick up capsule distensions more sensitively, while PDUS profits from the thin soft tissue on the dorsal aspect to detect hyperperfusion. As the high sensitivity for swelling on the volar side could previously be associated with a substantial amount of grade one GSUS findings of questionable relevance, the higher concordance between GSUS and PDUS by a dorsal view on MCP and PIP joint is a strong argument in favor of this examination technique as the most valuable in patients with RA. Longitudinal analysis is underway to clarify each approach in terms of significance for remission and treatment decisions. Disclosure of Interest: None Declared